We Scrub Your Tub. We Work Hard So You Don't Have To - Dow Chemical Company (1988)
Color print advertisement for Dow Bathroom Cleaner featuring a close-up view of the Scrubbing Bubbles mascot.
Keywords: Dow Chemical Company; Corporations; Chemical industry; Advertising; Cleaning compounds; Cleaning; Consumer goods